2022
DOI: 10.1002/cpt.2670
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Hepatic and Renal P‐gp/BCRP Inhibition of Drugs: An International Transporter Consortium Perspective

Abstract: The role of P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) in drug-drug interactions (DDIs) and limiting drug absorption as well as restricting the brain penetration of drugs with certain physicochemical properties is well known. P-gp/BCRP inhibition by drugs in the gut has been reported to increase the systemic exposure to substrate drugs. A previous International Transporter Consortium (ITC) perspective discussed the feasibility of P-gp/BCRP inhibition at the blood-brain barrier and its im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…The importance of P‐gp‐mediated efflux of drugs into bile has been demonstrated in rodent models (Hendrikx et al, 2013 ; Kong et al, 2016 ). Although many review articles state that P‐gp plays a key role in biliary excretion of P‐gp substrates in human subjects, actual data from human subjects are lacking (Taskar et al, 2022 ). In dogs, biliary excretion of the P‐gp substrate Tc 99m sestamibi is nonexistent in dogs lacking P‐gp and is severely blunted in dogs with acquired P‐gp deficiency, as well as dogs that are heterozygous for ABCB1‐1Δ as illustrated in Figure 2 .…”
Section: P‐gp and Drug Dispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of P‐gp‐mediated efflux of drugs into bile has been demonstrated in rodent models (Hendrikx et al, 2013 ; Kong et al, 2016 ). Although many review articles state that P‐gp plays a key role in biliary excretion of P‐gp substrates in human subjects, actual data from human subjects are lacking (Taskar et al, 2022 ). In dogs, biliary excretion of the P‐gp substrate Tc 99m sestamibi is nonexistent in dogs lacking P‐gp and is severely blunted in dogs with acquired P‐gp deficiency, as well as dogs that are heterozygous for ABCB1‐1Δ as illustrated in Figure 2 .…”
Section: P‐gp and Drug Dispositionmentioning
confidence: 99%
“…Despite the fact that P‐gp is expressed on renal tubules, and that P‐gp mediated efflux has been demonstrated in renal tubule cell culture studies, the authors could not identify a single study in human subjects that demonstrated an important role for P‐gp in renal drug excretion. In fact, the International Transporter Consortium recently concluded that there is little clinical risk of drug–drug interactions based on P‐gp inhibition of renal excretion (Taskar et al, 2022 ). The role of P‐gp in renal drug excretion in the dog and cat has not been investigated.…”
Section: P‐gp and Drug Dispositionmentioning
confidence: 99%
“…The increase in active efflux of a drug by ATP-binding cassette (ABC) transporters appears to be a major contributor to acquired resistance, among the various mechanisms associated with MDR such as the decline in drug uptake, cell cycle progression, drug metabolism, augmented DNA repair, and decreased apoptosis. P-glycoprotein (P-gp/ABCB1/MDR1) is the most common ABC transporter that causes MDR in the superfamily of ABC transporters (Taskar et al 2022 ). Over the past 30 years, there have been three generations of P-gp modulators developed as a result of research on the reversal of MDR; due to a variety of reasons, however, these modulators failed to show effectiveness in clinical trials.…”
Section: New Opportunity Of Peptidomimetic For Cancer Drug Resistancementioning
confidence: 99%
“…Gemfibrozil glucuronide is probably the most well‐known example which contributes to the gemfibrozil inhibitory effect on OATP1B in humans and can explain some FNs based on the in vitro effect of gemfibrozil alone 9 . Another example is norverapamil, a metabolite with AUC comparable to verapamil, which is a well‐known inhibitor of P‐gp 10 . However, no clear recommendations are currently available on when in vitro experiments are needed to evaluate the inhibitory potential of a metabolite toward transporters.…”
Section: Importance Of Metabolites In Transporter‐mediated Ddismentioning
confidence: 99%
“…9 Another example is norverapamil, a metabolite with AUC comparable to verapamil, which is a well-known inhibitor of P-gp. 10 However, no clear recommendations are currently available on when in vitro experiments are needed to evaluate the inhibitory potential of a metabolite toward transporters. A reasonable starting point may be focusing on major metabolites (exposure ≥10% of total drug-related material based on radioactivity measurement in systemic circulation from mass balance studies).…”
Section: Importance Of Metabolites In Transporter-mediated Ddismentioning
confidence: 99%